Perry Mason. The complete first season [videorecording (DVD)] - Jones, Rolin; Fitzgerald, Ron (Screenwriter) (Home Box Office, Inc., 2020)
Set in 1932 Los Angeles, this series will focus on the origin story of famed defense lawyer Perry Mason, based on characters from Erle Stanley Gardner's novels.